Epidemiology of back pain in German elite athletes - Trompeter, K.; Fett, D.; Platen, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The importance of physical activity in the treatment of back pain (BP) is generally accepted. However, an increase in physical activity has been suggested to be both a preventive factor and a possible risk factor for BP. It is well known that sports participation generally influences our health in a positive way, but there is a lack of knowledge about the optimal dose-effect relation. There is evidence for an association between high physical workloads and back injury. In sports, BP is commonly reported to be a frequent disorder but it is still unclear if its prevalence is higher than in nonathletes. The aim of this investigation was to determine lifetime prevalence (LT), 12-months prevalence (12m-P) and point prevalence (PP) of BP in German elite athletes regarding the pain intensity and the exact localization at the spine. Methods: The study was designed as a cross-sectional survey among athletes competing at the national elite level in different sports. An online-based questionnaire was sent to N 4000 athletes from different sports disciplines by the German Olympic Sports Confederation. The questionnaire consisted of several validated questionnaires on BP (Nordic questionnaire [1], questionnaire for grading the severity of chronic pain [2]). Additionally a self-developed questionnaire focusing different aspects of training and competition was used to evaluate the athletic workloads. Results: A sample of N=1094 German elite athletes (583 females, 508 males, 20.7±5.0 years, 176.6±10.5 cm, 70.6±14.1 kg, training volume: 18.3±7.9 hours/week) took part in the survey (response rate 25%). LT of BP was 88.7%, 12-mP was 81.4% and PP was 49.2%. The most often occurred localization was the lower back with a LT of 77.6%, 12m-P of 65.5% and PP of 33.8%. Regarding the sports disciplines individually LT of BP and low back pain ranges 57.9-100% and 42.1-92.9%, respectively. Very high prevalence rates of 94.7-100% were found in canoeing, dancing, rowing and water-polo. Discussion: The results of this investigation indicate that BP is a present problem in German elite athletes. Especially sports disciplines with high mechanical loads on the spine seem to be affected. High training volume up to 45 hours per week might be responsible for high prevalence rates. The results of this investigation underline the necessity of BP prevention in German elite athletes.